Analisis Pemeliharaan Battery Menggunakan Metode Reliability Mapping Pada Pesawat A330-900 - Bilhaq, Muhammad Kevin; Arifin, Mufti (Jurnal Teknologi Kedirgantaraan, 2024)
Airplanes is transportation that need a high level of safety and comfort. Therefore, the aircraft's parts must be in excellent shape and able to fly. This study aims to assess the reliability of battery maintenance on A330-900 aircraft using the reliability mapping method, as well as to assess the efficiency of doing so in order to compare the reliability mapping method's implementation to maintenance schedules for the batteries on these aircraft. The stages of this study started with gathering maintenance information for the A330-900, then went on to classify the different types of maintenance and create reliability mapping tables. Additionally, a comparison between the implementation and maintenance schedule for the A330-900 aircraft battery was made in order to analyze the reliability of battery maintenance on the A330-900 aircraft and to determine the effectiveness of using the reliability mapping method. After that, carry out reliability mapping optimization computations till conclusions about the research's findings are reached. Reliability mapping makes it evident where and when unforeseen maintenance takes place. The fact that just 3 unscheduled maintenance visits totaling 5.5% of the total maintenance were made out of the 54 replacements shows how dependable the battery maintenance on the A330-900 is. The execution of battery maintenance is reportedly wrong, with numbers based on estimations made according to calendar time being 77% early, 19% late, and 4% accurate